Eating and cooking loss characteristics of electrically stimulated and hot boned bull inside round muscle chilled at different rates - Shivas, S.D.; Kastner, Curtis L.; Dikeman, Michael E.; Hunt, Melvin C.; Kropf, Donald H. (Kansas State University. Agricultural Experiment Station, 2010)
We found steaks cut from inside rounds (chilled fast or slow) of electrically stimulated and hot boned bull carcasses, to be similar to conventionally processed steaks in taste panel, shear force and cooking loss characteristics.
Keywords: Beef; Electrically stimulated; Hot boned; Chiling